Design and Implementation of 12-Bit Arithmetic Logic Unit with 8 Operation Codes to Field Programmable Gate Array - Sumari, Arwin Datumaya Wahyudi; Hijriana, Sukriya; Dermawan, Denny (ELKHA : Jurnal Teknik Elektro, 2023)
Digital system has been a part of human life since the invention of the computer with a microprocessor as the central brain. At the heart of a processor is an Arithmetic Logic Unit (ALU) that handles arithmetic and logic operations. The need for high-speed computation to handle complex computations demands microprocessors with higher performance. The existing 4-opcode 8-bit ALU cannot handle multiplication operations, so a solution is needed. In this research, while raising the appeal of beginners, a 12-bit ALU with eight operation codes (opcode) was designed and implemented in Xilinx"™s Field Programmable Gate Array using a schematic diagram approach through logic gates. The designed and implemented ALU provides addition, subtraction, multiplication, square, AND, OR, NAND, and XOR operations. The multiplication operation was tested by performing the computation to provided datasets to obtain the distance travelled by ten military aircraft based on their maximum speed and air travel duration to ensure its performance. The computation performance comparison with an 8-bit ALU with four opcodes was also done. The computation was done for air travel between 10 to 60 minutes with a 10-minute difference. It was found that the 12-bit ALU with eight opcodes outperformed its contender with computation differences between 130.815 ns and 1,468.214 ns. This high performance is supported by the multiply operation that does repeated addition at one time. Based on this finding, the 8-opcode 12-bit ALU is more efficient in the context of computation time, with consistent accuracy. Moreover, the computation time required to calculate military aircraft data with different maximum speeds and air travel duration is only 119.501 ns.